2021
DOI: 10.1016/j.ajpath.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Functions of the Polycomb Group Protein EZH2 in Breast Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 98 publications
0
22
1
Order By: Relevance
“…The automethylation of EZH2 is reported as a self-activating mechanism for PRC2 [38]. However, in the current study we found that SUZ12 was not binding with EZH2, indicating the PRC2-independent action of EZH2 in PDAC as reported in breast cancer [49]. Interestingly, although nuclear p-STAT3 was involved in EZH2 transactivating action, p-STAT3 as well as STAT3 were not methylated in PDAC, which is different from other cancer cell types that methylated STAT3 by EZH2 is involved in tumorigenesis of glioblastoma stem-like cells [14].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The automethylation of EZH2 is reported as a self-activating mechanism for PRC2 [38]. However, in the current study we found that SUZ12 was not binding with EZH2, indicating the PRC2-independent action of EZH2 in PDAC as reported in breast cancer [49]. Interestingly, although nuclear p-STAT3 was involved in EZH2 transactivating action, p-STAT3 as well as STAT3 were not methylated in PDAC, which is different from other cancer cell types that methylated STAT3 by EZH2 is involved in tumorigenesis of glioblastoma stem-like cells [14].…”
Section: Discussioncontrasting
confidence: 71%
“…Overall, EZH2 permits transactivation of TPH1 and 5-HT 7 , allowing the TPH1-5-HT-5-HT 7 axis to stimulate PI3K/Akt and JAK2/STAT3 pathways in a feed-forward manner in PDAC, leading to maintenance of pancreatic CSC populations and drug resistance. The transactivation of TPH1 and 5-HT independent action of EZH2 in PDAC as reported in breast cancer [49]. Interestingly, although nuclear p-STAT3 was involved in EZH2 transactivating action, p-STAT3 as well as STAT3 were not methylated in PDAC, which is different from other cancer cell types that methylated STAT3 by EZH2 is involved in tumorigenesis of glioblastoma stem-like cells [14].…”
Section: Discussionmentioning
confidence: 78%
“…EZH2 drives oncogenesis not only in a canonical H3K27me3-dependent manner but also through non-canonical H3K27me3-independent functions. , For example, EZH2 has been shown to methylate non-histone proteins such as GATA4, STAT3, and β-catenin, among others. EZH2 can also act as a transcriptional activator by direct binding to a promoter region of several targets, such as NOTCH1 and TRIM28 .…”
mentioning
confidence: 99%
“…[44][45][46] In addition to upregulation of NOTCH1 resulting in stem cell expansion, EZH2 has been shown to directly promote invasion and metastasis by forming a complex with the cytoskeletal protein vinculin. 29,47 Our results suggest that EZH2 may therefore play a central role in chemotherapy-mediated cancer cell dissemination during NAC.…”
Section: Discussionmentioning
confidence: 75%